Micro entrepreneurship in the care sector: motives, values and practices. (1st November 2019) - Hall, Kelly; Needham, Catherine; Allen, Kerry
Abstract : This article uses qualitative interviews to explore the identity of care micro enterprises, focusing on the motives, values and practices of the people who set them up (the 'micro entrepreneurs'). It draws on a bricolage framework to demonstrate how they use local resources and networks, as well as traits of creativity and improvisation, to overcome limitations and get ahead within a turbulent and under-resourced social care sector. In doing so, it contributes to debates on hybridity, in particular the internal and external conflicts that hybrid organisations like micro enterprises face when managing competing social and market logics.